Mountain lake development by active tectonics and landslides in the North-Central Alborz (Northern Iran) - Ghassemi, Mohammad R.; Heydari, Maryam; Preusser, Frank (Geomorphology, 2026)
Lakes in active mountain belts record hydrological and climatological conditions, mass movements, and seismic events that influence their development and demise. Four paleolakes on the northern watershed of the central Alborz Mountains are studied here for the first time to reveal their characteristics regarding basin fill attributes and understand the underlying mechanisms and events that actively contributed to their evolution. The complex and unexplored interplay of heavy landslides, earthquakes, and actively deforming structures caused blockages of the mountain passages that formed the paleolakes at different times. Luminescence dating of the basin sediments reveals that the paleolakes formed between the late Middle Pleistocene and Early Holocene. Our geochronological results indicate that the four paleolakes formed primarily during glacial periods, specifically Marine Isotope Stages (MIS) 6 and 2, with only one showing earlier development during the interglacial periods, MIS 7 and MIS 5. As such, they were exposed to cold climatic conditions and were ice-covered, at least during the winter, in accordance with Alpine lakes. Overspill and breaching of the lakes were likely associated with catastrophic flooding downstream of the basin outlets, as exemplified by the Kojur paleolake and its outburst material, which formed the Sisangan alluvial fan. Sedimentary and incision characteristics of the region under study reveal that some paleolakes experienced more than one episode of damming and overspill. Future studies may provide more detailed insights into the formation and development of these lakes over time.